Synthesis and characterization of antimony tartrate for ceramic precursors - Mazali, I. O.; Las, W. C.; Cilense, M. (Consultants Bureau, 1999)
Synthesis and characterization of antimony tartrate used as a precursor of ceramic powders obtained by Pechini's method were carried out. Antimony tartrate was chosen as a substitute for the antimony citrate commonly used in this chemical processing, because of difficulties in preparing the citrate. FTIR and TGA/DTA analysis showed that antimony tartrate, H-2[Sb-2(C4H2O6)(2)]. forms a polymeric structure. The procedure described indicates that the antimony chelate obtained is adequate for Pechini's method.
Keywords: Pechini's method; chemical synthesis; antimony tartrate; characterization; ceramic precursor